Touching the Future: Drivers of E-Wallet Adoption in Malaysia - Ibrahim, Haslindar; Kuek, Thiam Yong; Kumar, Owenish A/L Shashi; Ong, Zi Jin; Ooi, Zhi Ling; Peh, Jia Xuan; Yhee Ho, Penny Shuen; Ali, A. J.; Kee, Daisy Mui Hung (Journal of The Community Development in Asia, 2025)
Touch ‘n Go is a Malaysian digital wallet app that offers secure, convenient and cashless transactions for users. It allows people to make payments through their smartphones anywhere in the country, including retail stores, restaurants and transportation hubs. Thus, this paper aims to study the factors that affect the adoption of e-wallets in Malaysia. In our research, a survey will be conducted using Google Forms for data collection. We have sent a survey to our target respondents, people who are using Touch ‘n Go e-Wallet. Our research aims to find out whether perceived convenience, perceived security, consumer attitudes and social influence will affect the intention of consumers to use Touch ‘n Go e-Wallet. Our findings show that perceived convenience and customer attitudes have a significant positive impact on the adoption of e-wallets while perceived security and social influence play a minimal role only. These findings highlight the importance of usability, user experience and trust-building strategies. Thus, Touch ‘n Go Sdn Bhd may improve the adoption of e-wallets among Malaysians in the future by focusing on these aspects.